Inovasi Pembelajaran Pendidikan Agama Islam Berbasis Blended Cooperative E-Learning Di Masa Pandemi - Nur Irsyadiah; Ahmad Rifa’i (Syntax Idea, 2021)
The purpose of this research is to find pai learning strategies and ways by using blanded e cooperative e learning methods. The research method used is qualitative research method by observing directly the implementation ofdefensejaran jaurak far in muhammadiyah college branch senen jakarta pusat. The results showed that blanded cooperative e learning method is the ideal solution in dealing with pandemic covid 19. Because this method can bridge the gap between students who have technological means and who do not have them. The combination of cooperative learning and blended learning approaches not only equips students with the ability to understand the material, but more than that can improve communication skills and interpersonal skills, problem solving, critical analysis and other skills needed by students. With the ease of technology, the limitations of classroom meetings can be solved by blended learning.